Homeopathic Potencies May Possess an Electric Field(-like) Component: Evidence from the Use of Encapsulated Solvatochromic Dyes - Cartwright, Steven J. (Homeopathy, 2020)
Background Homeopathic potencies have been shown to interact with a range of solvatochromic dyes to produce spectroscopic changes in the visible region of the electromagnetic spectrum. Furthermore, the nature of the changes observed under different experimental conditions is beginning to limit the number of possible hypotheses that can be put forward regarding the fundamental identity of potencies.Aims and Methods The present study uses β-cyclodextrins to encapsulate solvatochromic dyes of widely varying structures. The purpose of this approach is to de-couple the primary dye–potency interaction from any subsequent aggregation effects.Results Despite large differences in molecular structure between dyes, results show that potencies affect all dyes according to the same fundamental principles. Specifically, positively and negatively solvatochromic dyes collectively respond in opposite and complementary ways to potencies in accordance with the differential stabilisation of their excited and ground electronic states. Under the conditions of encapsulation, positively solvatochromic dyes display a bathochromic shift of, on average, 0.4 nm with a 2% absorbance change, and negatively solvatochromic dyes display a hypsochromic shift of, on average, 0.2 nm with a 1% absorbance change. This behaviour is only ever seen in two situations—where solvent becomes more polar or where an electric field is applied to solutions of dyes.Conclusions The conditions used in this and previous studies to investigate the interaction of potencies with solvatochromic dyes preclude increased polarity of solvent as being responsible for the observed effects and that an explanation in which potencies carry an electric field (or electric field-like) component is by far the more likely. From the magnitude of the spectral changes induced in the dye Brooker's merocyanine by Arsenicum 10M, an estimate of the strength of the postulated electric field of 1.16 × 107 V/m can be made, which is comparable with the potential difference across cell membranes.
Keywords: solvatochromic dyes; β-cyclodextrin; Arsenicum 10M; electric field; metastable state